Impact on teaching in times of COVID-19 pandemic: A qualitative study - Alejandro Almonacid-Fierro; Rodrigo Vargas-Vitoria; Ricardo Souza De Carvalho; Manuel Almonacid Fierro (International Journal of Evaluation and Research in Education (IJERE), 2021)
This article makes an analysis of the pedagogical teaching practices used and developed by Chilean physical education teachers during the coronavirus disease 19 (COVID-19) pandemic periods. The virus from China spread around the world, changed our daily lives and as such, at the same time impacted the educational system in a matter of weeks. Confinement led educational systems to eliminate face-to-face and use virtual teaching in order to continue with the teaching-learning processes, including the physical education discipline. From the methodological point of view, the study is installed in the interpretive-qualitative perspective, in such a way that 14 semi-structured interviews were carried by physical education teachers from the Maule-Chile region, via team, Zoom, Skype, because of the pandemic, face-to-face contact was impossible. The result of the study shows the impact on the quality of life of teachers and students because of the confinement. The pedagogical reconfiguration that teachers experienced in a matter of days, led them to use different virtual platforms to continue connected with their students, in order to deploy the learning objectives defined by the Chilean Ministry of Education. However, the foregoing shows the scarce possibility of verifying student learning, due to the difficulties of monitoring and feedback.